MANAJEMEN SISTEM PENDIDIKAN NASIONAL (Strategi dan Upaya menghadapi Tantangan Globalisasi melalui Pendidikan) - Asiyah Asiyah (Universitas Islam Negeri Fatmawati Sukarno, 2017)
The management of national education is essentially an integral part of the education management system and process as a whole in achieving national education and development goals. Government policies and efforts are proposed by experts in addressing national education management issues. Implementation of basic education seen from various aspects, politics, technical education, culture and professional, it is clear that the problem of basic educa- tion management is not a small problem and cannot be placed in a simple dichotomy: centralistic vs. decentralistic. A centralized education management system has been shown to have made little progress in improving the quality of education in general. Even in certain cases, centralized management has resulted in the sterilization of creativity in edu- cational units of various types and levels of education. To overcome the stagnation in the field of education is required a new paradigm in the field of education.